1998
DOI: 10.1021/jp980266g
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Scale Organization of Ethylene Oxide Surfactants on Graphite, Hydrophilic Silica, and Hydrophobic Silica

Abstract: To better understand the role of the interactions between surfactant, solvent, and a solid substrate on surface aggregation, we have studied the adsorption of a series of alkylpoly(ethylene oxide) C n E m surfactants on three different substrates: graphite, hydrophilic silica, and hydrophobic silica. Using atomic force microscopy (AFM), we find that adsorption to hydrophilic silica, with two exceptions, results in the formation of globular structures that are similar to bulk micelles. On silica that has been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
267
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(287 citation statements)
references
References 15 publications
(35 reference statements)
19
267
0
1
Order By: Relevance
“…First, is the affinity of the alkyl tails to the surface which is driven by the minimisation of graphene/graphite-water interfacial energy as a result of hydrophobic interactions. The second is a preferred orientation of the alkyl chains with the surface lattice because the carbon position in the alkyl chains is closely matched with the graphene surfaces [105,108,116,117,138,139]. The π-π interactions infer face-to-face stacking (see Fig.5A) of the surfactant containing aromatic ring(s) and the graphene basal planes involved in the non-covalent interactions [151], although the nature of this remains controversial [152,153].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…First, is the affinity of the alkyl tails to the surface which is driven by the minimisation of graphene/graphite-water interfacial energy as a result of hydrophobic interactions. The second is a preferred orientation of the alkyl chains with the surface lattice because the carbon position in the alkyl chains is closely matched with the graphene surfaces [105,108,116,117,138,139]. The π-π interactions infer face-to-face stacking (see Fig.5A) of the surfactant containing aromatic ring(s) and the graphene basal planes involved in the non-covalent interactions [151], although the nature of this remains controversial [152,153].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Considerably fewer experiments have been performed to explore the aggregation behavior of nonionic surfactants on hydrophilic surfaces. Nonionic ethylene oxide surfactants have been observed to form either globular aggregates or continuous bilayer structures on hydrophilic silica [7].…”
Section: Introductionmentioning
confidence: 99%
“…54 A strictly nonionic system that has been widely studied in the past is the adsorption of polyethyleneoxide (PEO)-based surfactants on silica. A recent AFM study 55 has shown that many of these surfactants make globular (roughly spherical) aggregates on the silica surface, with the spheres randomly arranged on the silica surface at nearestneighbor distances somewhat greater than twice the surfactant length. As with ionic surfactants on silica, these interfacial aggregates reflect bulk micelle morphology.…”
Section: Nonionic and Zwitterionic Surfactants On Hydrophilic Surfacesmentioning
confidence: 99%
“…56 PEO-based surfactants with relatively longer tailgroups or shorter headgroups, which have a tendency towards bilayer structures in solution, showed similar tendencies on silica. 55 …”
Section: Nonionic and Zwitterionic Surfactants On Hydrophilic Surfacesmentioning
confidence: 99%
See 1 more Smart Citation